Analisis Sosial Ekonomi Pedagang Pakaian di Blok D Pasar Ki Lemah Duwur Bangkalan Selama Pandemi Covid-19 - Mulya Arif; Manah Tarman; Subandy Widjaya (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to find out how the socio-economic conditions of clothing traders in Block D of the Ki Lemah Duwur Bangkalan market during the Covid-19 pandemic. This study uses a descriptive qualitative research method which aims to get a clear picture of the socio economic conditions of clothing traders in the Ki weak Duwur Bangkalan market during the Covid-19 pandemic. The technique of determining informants is perposive sampling to collect data through observation and interviews. The results of this study indicate that before the pandemic the level of income earned by clothing traders at the Ki Lemah Duwur Bangkalan market was able to meet their daily needs, However, after the pandemic, their income decreased drastically so that they could not fulfill their daily needs.